2000
DOI: 10.1002/(sici)1098-2396(20000315)35:4<300::aid-syn8>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Presence of NMDA-type glutamate receptors in cingulate corticostriatal terminals and their postsynaptic targets

Abstract: The glutamatergic projection from the anterior cingulate cortex to the medial caudate-putamen nucleus (CPN) has been implicated in motor and cognitive functions, many of which are potently modulated by activation of N-methyl-D-aspartate subtype of glutamate receptors (NMDARs). To determine the functional sites for NMDAR activation within this circuitry, we combined anterograde transport of biotinylated dextran amine (BDA) from deep layers of the rat anterior cingulate cortex with immunogold labeling of NMDAR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
2

Year Published

2001
2001
2007
2007

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 74 publications
0
16
2
Order By: Relevance
“…5, C and F). It is noteworthy that these changes in glutamate receptor expression occurred predominantly in olfactory-associated nuclei and also within the cingulate cortex, which provides excitatory input to the basal ganglia (Wang and Pickel, 2000). Therefore, we next analyzed markers of the dopaminergic system and found that 12 days of treatment with MTEP led to a significant increase in DAT binding (ϩ9%, t 74 ϭ 2.691, p ϭ 0.0088; Fig.…”
Section: Resultsmentioning
confidence: 93%
“…5, C and F). It is noteworthy that these changes in glutamate receptor expression occurred predominantly in olfactory-associated nuclei and also within the cingulate cortex, which provides excitatory input to the basal ganglia (Wang and Pickel, 2000). Therefore, we next analyzed markers of the dopaminergic system and found that 12 days of treatment with MTEP led to a significant increase in DAT binding (ϩ9%, t 74 ϭ 2.691, p ϭ 0.0088; Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Decreased basal NAC glutamate levels and enhanced cocaine-stimulated glutamate release are neuroadaptations observed following repeated contingent or noncontingent cocaine administration (for reviews see Anderson and Pierce, 2005;Cornish and Kalivas, 2001;Vandershuren and Kalivas, 2000). PNS has been associated with increased NAC N-methyl-D-aspartate (NMDA) receptor expression Berger et al, 2002), which are found presynaptically on corticostriatal terminals (Gracy and Pickel, 1996;Wang and Pickel, 2000). Given that the majority of cortical inputs to the striatum are glutamatergic, increased numbers of presynaptically localized NMDA receptors could result in glutamate enhancing its own release and contribute to the phenotype of PNS.…”
Section: Influence Of Pns On Neurochemical Responses To Cocainementioning
confidence: 99%
“…Only scarce presynaptic NR1 or NR2A immunoreactivity is observed in the striatum (Bernard and Bolam, 1998;Fujiyama et al, 2004) (but see Wang and Pickel, 2000). Nevertheless, physiological studies indicate that striatal NMDA receptors are involved in the regulation of dopamine and glutamate release (e. g. Krebs et al, 1991;Micheletti et al, 1993;Morari et al, 1993;Cheramy et al, 1996;Sesack et al, 2003).…”
Section: Ionotropic Receptorsmentioning
confidence: 99%